TATA KELOLA PEMERINTAHAN PADA SEKTOR INFORMAL (STUDI PEDAGANG KAKI LIMA DI KABUPATEN NGAWI) - Novita Trisniawan; Teguh Yuwono; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
The presence of informal sector, particularly street vendors (PKL), is anunavoidable economic reality happening to nearly all regions in Indonesia thatneeds special attention. On one side, street vendors have brought problems relatedto urban planning, social, health domain and so forth. While on the other side,street vendors are highly needed by the community in terms of fulfilling their needsand reducing the government’s burden. If managed properly, street vendors areable to provide economic improvement and community welfare in a region. NgawiRegency is one region area inseparable from the presence of street vendors. Suchinformal sector has dominated centers of crowd in Ngawi Regency, includingNgawi Regional Square. Street vendors in Ngawi Regency also have also led tomany problems, such as disruption to the city’s immaculacy and congestion. Thisresearch is thereby aimed to more deeply examine the Informal Sector Governancein Ngawi Regency.The present research was conducted using combination method orcombining the qualitative and quantitative research with the use of observationdata, interview, documentation and questionnaire in order to explain the realsituation in details while using triangulation of data source, method and theory.Based on the research performed, the results obtained are: the conditionand presence of street vendors in Ngawi Regency are already in accordance withthe theory and concept of Informal Sector; and Ngawi Regency Government has apolicy plan to relocate street vendors. Legalistic approach employed to managestreet vendors is yet accurate, based on findings in the field. A combination ofempowerment, structuralist and legalistic approaches is recommended in themanagement of street vendors.Keywords: Street Vendors, Policy, Governance Approach